Eksistensi Nilai Moral Bushido pada Budaya Kerja di Jepang dan Etos Kerja Profesional di Indonesia: The Existence of Bushido Moral Values in Japanese Work Culture and the Professional Work Ethic in Indonesia - Isnaeni Khurniya Falakhiya (Jurnal Pendidikan Bahasa Jepang Undiksha, 2026)
Work ethic is an important factor that influences workers' mindsets in carrying out their jobs. The work ethic in Japan and Indonesia is quite different from each other. In this case, research related to the existence ofwork ethic is important to study. This can be used as a guideline and evaluation of the work ethic in the country where the workers are located.This study focuses on a contrastive analysis by comparing the existence ofvalues or work ethic in Japan and Indonesia. This studyuses a descriptive qualitative approach. Data was obtained from questionnaires andinterviews conducted with Indonesian workers in Japan and workers in Indonesia. The results show that work ethic is influencedby many factors, such as the length of time a person has been working, their level of discipline, andtheir compliance in accepting the values inherent in the work ethic. Based on the results of the interviews, workers in Japan showed a more disciplined andobedient work ethic and were able to apply the values of bushido in their work. Meanwhile, most workers in Indonesia have not yet applied the moral values of professionalism in their work. Thus, the work ethic in Indonesia has not yet been consistently implemented at an optimal level.